Perancangan Arsitektur Data Warehouse Pada Industri Perkebunan Kelapa Sawit - Ahmad Fahmi Karami (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The palm oil industry, one of the leading industry in Indonesia must continue to grow even faced with the moratorium policy from Presidential Instruction. The strategy implemented is improving the company's operational performance, supported by a data warehouse that can provide information that help company making a decision. The strategy set includes productivity, efficiency, and optimization. The data warehouse architecture is designed to fulfill the defined strategies. The results showed that the hub-and-spoke type of architecture is suitable for implementing the company's strategy.